2013
DOI: 10.1039/c3cs60232j
|View full text |Cite
|
Sign up to set email alerts
|

Engineering metal-based luminescence in coordination polymers and metal–organic frameworks

Abstract: The rapidly growing number of luminescent coordination polymers (CPs) and metal-organic frameworks (MOFs) illustrates high interest as well as accessibility of such materials. The interplay between inorganic and organic components in these materials offers a large number of viable luminescence processes. The enormous variability of available ligand-metal combinations opens the possibility of creating luminescence "by design", based on a proper understanding of the processes involved. Together with the multifun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
442
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 928 publications
(450 citation statements)
references
References 52 publications
5
442
1
2
Order By: Relevance
“…The most representative examples are water induced luminescence quenching of lanthanide metal based MOFs,87 because their luminescence directly emit from the oxophilic lanthanide ions which have strong coordination ability for H 2 O,88, 89, 90 and the high‐energy O–H oscillators can effectively match electronic energy gaps of the lanthanide ions 91…”
Section: Coordinative Guestsmentioning
confidence: 99%
“…The most representative examples are water induced luminescence quenching of lanthanide metal based MOFs,87 because their luminescence directly emit from the oxophilic lanthanide ions which have strong coordination ability for H 2 O,88, 89, 90 and the high‐energy O–H oscillators can effectively match electronic energy gaps of the lanthanide ions 91…”
Section: Coordinative Guestsmentioning
confidence: 99%
“…Undoubtedly, the most desired property in order to allow the accommodation and retainment of chemical entities as, for instance, in the storage of gases (e.g., H 2 , CH 4 ), 68,69 capture of CO 2 , 70 removal of toxic gas molecules 71 and inclusion of biologically active species. 16 In this context, a great evolution have been observed concerning the pore/cage sizes ( Figure 2) leading to the isolation of several highly porous MOF structures over the years ( Figure 3); ii) Catalytic activity, in order to convert chemical species, some of them dangerous for humans and environment, into others which are significantly more safe or with industrial interest; 72 iii) Luminescence, a phenomenon which results from the emission of radiation from vibrationally or electronically excited species; 21,23 iv) Magnetism, which depends on the nature and spatial relation of both metallic centres and organic linkers, and the organizational level originated by the ligand-metal coordination. …”
Section: -Applicabilitymentioning
confidence: 99%
“…10,15 MOF investigation is also spread over different advanced bew fields such as biomedicine, 16 magnetism, 17,18 conductivity, 10,19 fabrication of membranes, 20 or light-based devices. [21][22][23][24] This review does not intend to be not an exhaustive survey literature describing minutely the basic concepts, primary building blocks (PBUs, i.e., organic linkers and metallic centres), topologies and structural features as well as all the intrinsic properties of MOFs. For this purpose there are several interesting dedicated reviews reported over the last few years, for which we strongly encourage direct the reader.…”
Section: -Introductionmentioning
confidence: 99%
“…The emission spectra are composed of two major independent components, which could be visualized by the deconvolution of the curves (See Figures S9-S12, supplementary materials). Zinc(II) and cadmium(II) cations (as well as the other metal cations with complete electron shell configuration) are known not to interfere with the ligand-centered luminescence [48], therefore, these two components could be assigned to the terephthalate anion and the imidazolyl moiety, respectively [49,50]. The position of the luminescence emission spectra peak for terephthalate anion is consistent among all four compounds (423-430 nm).…”
Section: Luminescence Propertiesmentioning
confidence: 69%